Effects of starch nanoparticle-stabilized oleic acid emulsions and warm storage on the structural properties and starch digestibility of cooked rice - Ah-In Kim; Jae Young Park; Hyun Ho Bae; Sang Min Cha; Jong-Yea Kim; Ju Hun Lee; Eun Young Park; Hyun-Jung Chung (Food Research International, 2026)

Inkjet-printed full-color tandem quantum dot light-emitting diode with dual-color subpixels - Young-Jae Ko; Gyu-jin Shin; Hyo-Bin Kim; Seung-Ah Lee; Jae-In Yoo; Jun Hyup Lee; Jang-Kun Song (Chemical Engineering Journal, 2026)

Childhood exposure to traffic-related air pollution and lung function at age 10 years: evidence of nutritional modification in a birth cohort - Yujin Park; Dong-Wook Lee; Choong Ho Shin; Young Ah Lee; Yun Jeong Lee; Dong In Suh; Yun-Chul Hong; Youn-Hee Lim; Bung-Nyun Kim; Johanna Inhyang Kim; Soontae Kim; Kyoung-Nam Kim (International Journal of Hygiene and Environmental Health, 2026)

Unravelling the Population Genetic Dynamics of the Ivory Snail (Babylonia areolata) in Vietnam: Guiding Sustainable Aquaculture Development - Sang Van Vu; Angkasa Putra; Sarifah Aini; Imon Abedin; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Thanh Tat Le; Hoang Huy Nguyen; Hien Van Doan; In Van Vu; Hyun-Woo Kim; et al. (Thalassas: An International Journal of Marine Sciences, 2026)

Interaction between ethanol and flunitrazepam in rats: Pharmacokinetic mechanisms and toxicological implications - Yejin Kim; Jeong In Seo; Jin Ah Won; Sooyeun Lee; Hye Hyun Yoo (Chemico-Biological Interactions, 2026)

Comparison of the Growth and Internal Quality of Red Radish (Raphanus sativus L. cv. Cherry One) Cultivated Under Different Hydroponic Systems and LED Light Qualities - Ah Young Shin; Joo Hwan Lee; Yong Beom Kwon; Yu Jin Kang; In-Lee Choi; Yongduk Kim; Jidong Kim; Ho-Min Kang (Horticulture, Environment, and Biotechnology, 2026)

Dyella stictolepturae sp. nov., isolated from the larva gut of red-brown longhorn beetle (Stictoleptura succedanea) - Bora Kim; Ah-In Yang; Sung-Hong Joe; Hae-In Joe; Na-Ri Shin (Antonie van Leeuwenhoek, 2026)

Hydramethylnon-induced autophagy and apoptosis in human bronchial epithelial cells by homeostatic changes - Yeon-Ho Kang; Sou Hyun Kim; Hye-Jin Jeong; Ah-Yoon Song; Hye-In Park; Eun-Hye Kim; Young-Suk Jung; Yong Joo Park (Toxicology, 2026)

Continuous manufacturing and process analytical technology: focusing on dosage forms with improved solubility and controlled release - Su Hyun Seok; Seung-Dong Yoo; Dong‑Wook Kim; In-Ah Lee; Kyung Hyun Min; Ji-Hyun Kang; Chun-Woong Park; Ju-Young Kim; Eun-Seok Park (Journal of Pharmaceutical Investigation, 2025)

Reducing Healing Period with DDM/rhBMP-2 Grafting for Early Loading in Dental Implant Surgery - Jeong-Kui Ku; Jung-Hoon Lim; Jung-Ah Lim; In-Woong Um; Yu-Mi Kim; Pil-Young Yun (Tissue Engineering and Regenerative Medicine, 2025)
Background: Traditionally, dental implants require a healing period of 4 to 9 months for osseointegration, with longer recovery times considered when bone grafting is needed. This retrospective study evaluates the clinical efficacy of demineralized dentin matrix (DDM) combined with recombinant human bone morphogenetic protein-2 (rhBMP-2) during dental implant placement to expedite the osseointegration period for early loading. Methods: Thirty patients (17 male, 13 female; mean age 55.0 ± 8.8 years) requiring bone grafts due to implant fixture exposure (more than four threads; ≥ 3.2 mm) were included, with a total of 96 implants placed. Implants were inserted using a two-stage protocol with DDM/rhBMP-2 grafts. Early loading was initiated at two months postoperatively in the mandible and three months in the maxilla. Clinical outcomes evaluated included primary and secondary stability (implant stability quotient values), healing period, bone width, and marginal bone level assessed via cone-beam computed tomography. Results: All implants successfully supported final prosthetics with a torque of 50Ncm, without any osseointegration failures. The average healing period was 69.6 days in the mandible and 90.5 days in the maxilla, with significantly higher secondary stability in the mandible (80.7 ± 6.7) compared to the maxilla (73.0 ± 9.2, p < 0.001). Histological analysis confirmed new bone formation and vascularization. Conclusion: DDM/rhBMP-2 grafting appears to significantly reduce the healing period, enabling early loading with stable and favorable clinical outcomes.

A comparison of the nutritional quality of ready-to-cook meals and conventional home-cooked meals in Korea - Eunji Choi; Sung-Won Yoon; Jung-Ah Shin; In-Hwan Kim; Jeehye Sung; Jang-Hyuk Ahn; Hyun-Jeong Kim; Dong Won Seo; Sam-Pin Lee; Jo-Won Lee; Bo Kyung Moon; Sojung Kim; et al. (International Journal of Gastronomy and Food Science, 2024)

Effect of nitro-conjugated linoleic acid on the inflammatory response of murine macrophages activated with lipopolysaccharide derived from Prevotella intermedia - Jung Eun Lee; Ah Rim Lee; Eun-Young Choi; In Soon Choi; Sung-Jo Kim (Inflammopharmacology, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Multilayer composite membranes composed of carbon molecular sieve membranes sandwiched between stacked zeolite nanosheets - Dong Yun Han; Ah Hyun Lee; Su Kyung Kang; Se Wan Kim; Woo Chul Kwak; In-Seok Jeon; Seunghwa Yang; Pyung Soo Lee (Chemical Engineering Journal, 2024)

Nifedipine attenuates alveolar bone destruction and improves trabecular microarchitectures in mice with experimental periodontitis - Yohan Lee; Jung Eun Lee; Ah Rim Lee; Eun-Young Choi; In Soon Choi; Sung-Jo Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Association between SYVN1 and SEL1 genetic polymorphisms and remission in rheumatoid arthritis patients treated with TNF-α inhibitors: a machine learning approach - Woorim Kim; Ha Rim Yeon; Jun Hyeob Kim; Joo Hee Kim; Ji Hyoun Kim; Hyoun-Ah Kim; Ju-Yang Jung; Jinhyun Kim; In Ah Choi; Kyung Eun Lee (Immunologic Research, 2023)

Overexpression of Arabidopsis thaliana blue-light inhibitor of cryptochromes 1 gene alters plant architecture in soybean - Hyun Suk Cho; Yoon Jeong Lee; Hye Jeong Kim; Moon-Young Park; Wan Woo Yeom; Ji Hyeon Song; In Ah Kim; Seong-Hyeon Kim; Jeong-Il Kim; Young-Soo Chung (Plant Biotechnology Reports, 2021)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

Retained or altered expression of major histocompatibility complex class I in patient-derived xenograft models in breast cancer - In Hye Song; Young-Ae Kim; Hyeonjin Lee; Hye Seon Park; In Ah Park; Chan Kyu Sim; Myeong Sup Lee; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2019)

Reversine induces caspase-dependent apoptosis of human osteosarcoma cells through extrinsic and intrinsic apoptotic signaling pathways - Jae-Sung Kim; In-A Cho; Kyeong-Rok Kang; HyangI Lim; Tae-Hyeon Kim; Sun-Kyoung Yu; Heung-Joong Kim; Seul Ah Lee; Sung Min Moon; Hong Sung Chun; Chun Sung Kim; Do Kyung Kim (Genes & Genomics, 2019)

Effects of CYP2D6 and CYP3A5 genetic polymorphisms on steady-state pharmacokinetics and hemodynamic effects of tamsulosin in humans - Kyoung-Ah Kim; In-Bae Park; Ji-Young Park (European Journal of Clinical Pharmacology, 2018)

Anti-inflammatory Effects of Polyphenol Extracts from Ulva linza (Ulvophyceae, Chlorophyta) - Ju-Hyoung Kim; Shin Ae Kim; Matthew S. Edwards; In-Ah Lee (Toxicology and Environmental Health Sciences, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

IAA-producing Klebsiella variicola AY13 reprograms soybean growth during flooding stress - Ah-Young Kim; Raheem Shahzad; Sang-Mo Kang; Chang-Woo Seo; Yeon-Gyeong Park; Hyun-Jin Park; In-Jung Lee (Journal of Crop Science and Biotechnology, 2017)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Oncogenic role of SIRT1 associated with tumor invasion, lymph node metastasis, and poor disease-free survival in triple negative breast cancer - Soo Young Chung; Yoon Yang Jung; In Ae Park; Hyojin Kim; Yul Ri Chung; Ji Young Kim; Soo Young Park; Seock-Ah Im; Kyung-Hun Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han; et al. (Clinical & Experimental Metastasis, 2016)

Enterobacter sp. SE992-induced regulation of amino acids, sugars, and hormones in cucumber plants improves salt tolerance - Sang-Mo Kang; Ramalingam Radhakrishnan; Seok-Min Lee; Yeon-Gyeong Park; Ah-Yeong Kim; Chang-Woo Seo; In-Jung Lee (Acta Physiologiae Plantarum, 2015)

Relationship between cold hardiness and dehydrin gene expression in peach shoot tissues under field conditions - Hyunsuk Shin; Sung-Il Oh; Min-Ah Kim; Seok Kyu Yun; Youngjae Oh; In-Chang Son; Hong-Sig Kim; Daeil Kim (Horticulture, Environment, and Biotechnology, 2015)

Capsaicin suppresses the migration of cholangiocarcinoma cells by down-regulating matrix metalloproteinase-9 expression via the AMPK–NF-κB signaling pathway - Gong-Rak Lee; Soo Hwa Jang; Chang Jae Kim; Ah-Ram Kim; Dong-Joon Yoon; Neung-Hwa Park; In-Seob Han (Clinical & Experimental Metastasis, 2014)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

The green algae Ulva fasciata Delile extract induces apoptotic cell death in human colon cancer cells - Min Ju Ryu; Areum Daseul Kim; Kyoung Ah Kang; Ha Sook Chung; Hye Sun Kim; In Soo Suh; Weon Young Chang; Jin Won Hyun (In Vitro Cellular & Developmental Biology - Animal, 2013)

Erratum to: Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekkhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Bifidobacterium longum HY8004 attenuates TNBS-induced colitis by inhibiting lipid peroxidation in mice - In-Ah Lee; Eun-Ah Bae; Jung-Hee Lee; Hoyong Lee; Young-Tae Ahn; Chul-Sung Huh; Dong-Hyun Kim (Inflammation Research, 2010)

Antiangiogenic and Apoptotic Properties of a Novel Amphiphilic Folate-Heparin-Lithocholate Derivative Having Cellular Internality for Cancer Therapy - Mi Kyung Yu; Dong Yun Lee; Yoo Shin Kim; Kyeongsoon Park; Soo Ah Park; Dai Hyun Son; Gee Young Lee; Jong Hee Nam; Sang Yoon Kim; In San Kim; Rang Woon Park; Youngro Byun (Pharmaceutical Research, 2007)

The influence of Ras pathway signaling on tumor radiosensitivity - In Ah Kim; Annemarie T. Fernandes; Anjali K. Gupta; W. Gillies McKenna; Eric J. Bernhard (Cancer and Metastasis Reviews, 2004)

Modulatory Properties of Various Natural Chemopreventive Agents on the Activation of NF-κB Signaling Pathway - Woo-Sik Jeong; In-Wha Kim; Rong Hu; Ah-Ng Tony Kong (Pharmaceutical Research, 2004)

Modulation of AP-1 by Natural Chemopreventive Compounds in Human Colon HT-29 Cancer Cell Line - Woo-Sik Jeong; In-Wha Kim; Rong Hu; Ah-Ng Tony Kong (Pharmaceutical Research, 2004)

Isolation and characterization of a novel rice Ca2 +-regulated protein kinase gene involved in responses to diverse signals including cold, light, cytokinins, sugars and salts - Kyung-Nam Kim; Jung-Sook Lee; Hee Han; Seung Ah Choi; Seung Joo Go; In Sun Yoon (Plant Molecular Biology, 2003)